Strategies to improve access to medicines in Peru - Ugarte Ubilluz, Oscar (2019)
The pharmaceutical market in Peru has doubled in recent years and contains public and private markets. The public market represents 70% of the total and the private market 30% as measured by units sold. But when measured by cost, public market is 30% and private market is 70%. The public market consists of three different sub-markets: 1) strategic medicines provided by the Peruvian state to all citizens like vaccines and others; 2) non strategic medicines, like most others provided by the public institutions; and 3) the critical sub-market, like oncologic medications, in which there is a high concentration of property that allows some companies to dominate the market. The analysis of diferent markets, public or private enables us to recognize different barriers to access such different strategies to improve access.